Knowledge, Competency, and Depression Among Multisectoral Community Mental Health Teams: A Cross-Sectional Study - Fajar Rinawati; Hengky Irawan; Muhammad Ali Sodik; Astri Yunita (Universitas Tribhuwana Tunggadewi, 2026)
Mental health problems have become an increasing global health challenge and are closely related to the achievement of the Sustainable Development Goals (SDGs), particularly Goal 3: Good Health and Well-Being, which emphasizes the importance of promoting mental health and psychological well-being for all individuals. Knowledge and ability in managing community mental health problems are important factors in the success of mental health services. Lack of competence may increase anxiety, which can eventually lead to depression among team members. This study aimed to analyze the relationship between knowledge and the ability to manage community mental health problems and depression levels among Community Mental Health Implementation Teams. This study used a quantitative correlational design with a cross-sectional approach. The population consisted of all Community Mental Health Implementation Team (TPKJM) members, totaling 184 individuals, and 64 respondents were selected using proportional simple random sampling. To ensure data quality, the questionnaire was tested for validity and reliability, yielding validity values above 0.516 and a Cronbach’s alpha of 0.96. Depression levels were measured using the Patient Health Questionnaire-9. The results showed that 98% of respondents had good knowledge, 95% had good ability, 44% had no depression, and 41% experienced minimal depression. The correlation test between knowledge and depression level showed a p-value = 0.024, while the correlation between ability and depression level showed a p-value of 0.036 (0.05). These findings indicate a significant relationship between knowledge and ability with depression levels among TPKJM members. Adequate knowledge and abilities among TPKJM members can help the team become more prepared and confident in carrying out their duties optimally, thereby reducing anxiety and minimizing depression.